Gaps in Hypertension Guidelines in Low- and Middle-Income Versus High-Income Countries: A Systematic Review. Issue 6 (December 2016) - Owolabi, Mayowa; Olowoyo, Paul; Miranda, J. Jaime; Akinyemi, Rufus; Feng, Wuwei; Yaria, Joseph; Makanjuola, Tomiwa; Yaya, Sanni; Kaczorowski, Janusz; Thabane, Lehana; Van Olmen, Josefien; Mathur, Prashant; et al.
Abstract : Supplemental Digital Content is available in the text.